An Epidemiological Assessment Of Healthcare-Associated Infections: The Impact Of Nursing Adherence To Medical Sterilization Protocols In Surgical Units (The Review of Diabetic Studies, 2025)
Healthcare-associated infections (HAIs), particularly surgical site infections (SSIs), remain a significant challenge in surgical units worldwide, contributing to increased morbidity, mortality, and healthcare costs. This paper presents an epidemiological assessment of HAIs in Saudi Arabian surgical settings, with a focused analysis on the critical role of nursing adherence to medical sterilization protocols. Despite Saudi Arabia's advanced regulatory frameworks, including the Central Board for Accreditation of Healthcare Institutions (CBAHI) and the General Directorate of Infection Prevention and Control (GDIPC), SSI rates remain elevated in several healthcare facilities, exacerbated by the presence of multidrug-resistant organisms such as MRSA and CRE.Through a review of epidemiological data and current infection control practices, this study highlights the knowledge-practice gap among nursing staff that impedes effective protocol compliance. Factors such as staffing shortages, burnout, and insufficient psychological support undermine adherence, directly impacting patient outcomes. The paper argues for systemic reforms that integrate behavioral health models, enhanced training, and sustainable staffing policies to strengthen nursing compliance.Findings emphasize that optimizing nursing adherence to sterilization protocols is essential for reducing the incidence of HAIs, improving surgical outcomes, and aligning with Saudi Vision 2030’s healthcare quality objectives. This assessment underscores the necessity of combining regulatory rigor with human-centered interventions to safeguard patient safety in surgical units across the Kingdom.